Exhuming the Role of Globe FM and Bauchi Radio Corporation (BRC) on Political Mobilization during the 2015 Presidential Election in Nigeria. - Bappayo, Abubakar; Kirfi, Yushau Haruna; Baba, Mustapha Abdulhamid (NIU Journal of Humanities; Vol 3 No 3 (2018): KIU Journal of Humanities, Vol. 3 No. 3, September 2018, 2018)
The research method used in this study was survey while questionnaire was the instrument of data collection. The sample size was 384 respondents selected from Bauchi and Yobe States. The sampling   technique was multi-stage. The results of this study found out that the respondents were exposed to political programmes from Globe FM than they were to those from BRC. The results of this study showed that the researcher concludes that most of the sample from Yobe and Bauchi States were exposed to political programmes from Globe FM and BRC very often within the election period hence they developed perceptions from these programmes. The conclusion of this study is that Globe FM fared better than BRC in the area of information and education about political issues and recommends that radio political programmes should provide educative content that enlightens the general public about political issues during elections rather than dancing to the tune of the stationsâ€™ proprietors. It is also recommended radio political programmes should continue to be tracking the performance of elected officials after electioneering as doing so will make the electorate politically active and make the elected officials accountable to the voters. Keywords: Exhuming, Radio, Political Mobilization and Election.